Vascularização de gemas florais de cafeeiro (Coffea arabica L.) em diferentes condições hídricas e hormonais - Mesa, Andrea Jaramillo (2020)
Coffee as a commodity has great demands for its commercialization and consumption every year and Brazil is considered the leading country in its production. However, one of the main problems that Brazilian coffee farming still faced is the lack of synchrony in the flowering process, because blossoms that occur in different periods, result in fruits with different degrees of ripeness, which increases the costs of the harvest, hindering the control of diseases, and changes the final quality of the coffee drink. Therefore, the present research provides new knowledge that contributes to the understanding of the problem of poor synchronization in floral development, with the aim to evaluate the development of vascularization in stages G3 and G4 (MORAIS et al., 2008) of floral buds of Coffea arabica L. under different conditions of water and hormones. Thus, by anatomical analyses the development of vascularization of floral buds of coffee trees under water deficit and irrigation treatments and the quantification of ethylene production of leaves and buds, in greenhouse conditions were evaluated. Also, it was evaluated the ethylene production and the development of vascularization of floral buds in stages G3 and G4 in the field, under treatments with exogenous applications of agents that simulate the biosynthesis of the ethylene hormone (Ethrel®), and the inhibition of ethylene action with 1-MCP (1-MCP + surfactant Break - thru®). The values resulting from the quantification of ethylene production (ppm g-1 h-1), during the evaluation of the different treatments showed a higher production in floral buds compared to the hormone production of leaves. In addition, the vascularization development of flower buds under irrigation was greater than flower buds under water deficit. Also, it was observed that the development of procambium was greater in floral buds treated with Break - thru®, which showed greater development and thickness of the procambial meristem. The correlation analysis showed a positive correlation between the procambium area and the ethylene production resulting from the experiment. In the treatment with Break - thru®, there was an average positive correlation (r = 0.87) and a strong positive correlation (r = 0.96), 15 and 30 days after application, respectively. Data indicate higher levels of ethylene and greater development of procambium in flower buds. Finally, the present work provides new information on the production of ethylene from leaves and floral buds of coffee trees under different water conditions in greenhouse, and the production of ethylene from coffee plants sprayed with agents that stimulate their biosynthesis or inhibit its action in the field.